Analisis Pasar dan Finansial Sebagai Penentu Keberlanjutan Usaha Mouthwash Tablet Berbahan Alami - Setiawati, Indah; Nafingah, Siti; Zahra, Ridha Aisya; Trilatifah, Fatmah; Musyarifah, Musyarifah; Sejati, Rafi Ashza (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The research aims to assist the development of innovative products into a viable business by knowing the competitor analysis, market opportunity analysis, and business financial analysis. Data was collected from direct observation in the market and secondary data from the marketplace. The analysis was carried out by looking at product competitors, consumer profiles, and formulas for determining HPP, BEP and simple cash flow. The results of the analysis show that the tablet mouthwash business has advantages over other similar products. In addition, the market opportunity for this product is promising among women. The results of the financial analysis show the sustainability of the business which is characterized by increasing profits each quarter.